Antidiarrhoeal Activity of Ethanolic Extract of Leaf Galls ’Kakadshringi’ in Swiss Albino Mice - S. Upadhye, Anuradha; A. Rajopadhye, Anagha; M. Mujumdar, Arvind (Asian Journal of Chemistry, 2010)
The ethnobotanical and ayurvedic literature indicated that 'Kakadshringi' leaf galls are used for the treatment of diarrhoea. During survey it was observed that source of 'Kakadshringi' is leaf galls on botanically three different plant species viz., Pistacia integrrima Stew. ex Brindis, Terminalia chebula Retz. and Garuga pinnata Roxb. In present work, the study intended to investigate the antidiarrhoeal activity of ethanolic extract of leaf galls used as 'Kakadshringi' in mice. The authenticated resources of 'Kakadshringi' were powdered, defatted and then HPTLC profile of potent extract was carried out using well established protocols as a part of standardization. Based on exploratory studies on petroleum ether and ethanolic extracts of all three samples using castor oil induced diarrhea further studies were carried out on Pistacia integrrima Stew. ex Brindis ethanolic extract. The ethanolic extract of Pistacia integrrima Stew. ex Brindis and loperamide showed significant reduction in fecal output in castor oil and magnesium sulphate induced diarrhoea and castor oil induced intraluminal fluid accumulation. The extract also inhibited dose dependently (100-500 mg/kg) the intestinal propulsion of charcoal meal in normal and barium chloride induced changes in gastrointestinal tract. The data obtained indicate that the ethanolic extract of Pistacia integrrima Stew. ex Brindis has antidiarrhoeal, antisecretory and antipropulsive activities. Based on these studies Pistacia integrrima Stew. ex Brindis can be equated to 'Kakadshringi' and its indication for the treatment of diarrhoea.